Social-Motor Coordination Between Peers: Joint Action Developmental Trajectories in ASD and TD. - Bar Yehuda, Shahar; Bauminger-Zviely, Nirit (Journal of Autism & Developmental Disorders, 2024)
Coordinating a physical movement in time and space with social and nonsocial partners to achieve a shared goal – "joint action" (JA) – characterizes many peer-engagement situations that pose challenges for individuals with autism spectrum disorder (ASD). This cross-sectional study examined development of JA capabilities comparing ASD versus typically developing (TD) groups in early childhood, preadolescence, and adolescence while performing mirroring and complementing JA tasks with social (peer) and nonsocial (computer) partners. Results indicated better motor coordination abilities on computerized tasks than in peer dyads, with larger peer-dyad deficits shown by the ASD group. Developmental growth in JA abilities emerged, but the ASD group lagged behind same-age peers with TD. Socio-motor interventions may offer new channels to facilitate peer engagement in ASD.